Faktor-Faktor Mempengaruhi Transaksi Non Tunai Mobile Banking di Bank Muamalat Medan - Muhammad Iqbal Sani; Saparuddin Siregar; M Marliyah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
The using of mobile banking facility as the efficiency in consument’s transaction at Bank of Muamalat should be paid attention. The easy of operasionalization and transaction of mobile banking as the day is support the consument at Bank of Muamalat Medan to use the facility non-cash. This research is to understand about: (1) as the relevant of the importance influence among usefulness factor, the easy of use, compatibility, credibility, risk, cost, and self ability toward on intention to use, transaction non cash of mobile Banking, (2) as the gathering the importance influence among usefulness factor, ease to use, compatibility, credibility, risk, cost, and self ability toward on intention to use, transaction non cash of mobile Banking. This research is using quantitative research by using double linier regression The population of this research is the customer of Bank of Muamalat around 830 people and the sample 126 people. The result of this research is showing the gathering of usefulness variable, easy of using, compatibility, credibility, risk, cost, and self ability toward on intention to use, transaction non cash of mobile Banking influence desiring to use the of mobile. As the relevant of usefulness, easy of use, compatibility, credibility, risk, cost, and self-efficacy toward on intention to use, transaction non cash of mobile Banking has the influence toward the variable of intention to use.